2014
DOI: 10.3920/bm2013.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and epigenetic regulation of inflammatory mediators in type 2 diabetes and obesity

Abstract: Metabolic syndrome is associated with alterations in the structure of the gut microbiota leading to low-grade inflammatory responses. An increased penetration of the impaired gut membrane by bacterial components is believed to induce this inflammation, possibly involving epigenetic alteration of inflammatory molecules such as Toll-like receptors (TLRs). We evaluated changes of the gut microbiota and epigenetic DNA methylation of TLR2 and TLR4 in three groups of subjects: type 2 diabetics under glucagon-like pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 54 publications
4
69
0
4
Order By: Relevance
“…Particularly, Crohn's disease may be caused or aggravated by bacteria like Firmicutes (Fecalibacterium prausnitzii) and Escherichia coli [35]. Evidence exists that Firmicutes:Bacteriodetes ratio is elevated in irritable bowel syndrome, obesity, type 2 diabetes mellitus (T2D) and insulin resistance [36]. It is unascertained why the same ratio has been found increased in old age [37], however a greater diversity of microbiota was associated with a healthier status in elderly with respect to that found in younger adults [38].…”
Section: Gut Microbiota: the Overcalled Cardmentioning
confidence: 99%
“…Particularly, Crohn's disease may be caused or aggravated by bacteria like Firmicutes (Fecalibacterium prausnitzii) and Escherichia coli [35]. Evidence exists that Firmicutes:Bacteriodetes ratio is elevated in irritable bowel syndrome, obesity, type 2 diabetes mellitus (T2D) and insulin resistance [36]. It is unascertained why the same ratio has been found increased in old age [37], however a greater diversity of microbiota was associated with a healthier status in elderly with respect to that found in younger adults [38].…”
Section: Gut Microbiota: the Overcalled Cardmentioning
confidence: 99%
“…43 Moreover, the methylation of 7 CpGs in the promoter of the gene coding for the inflammatory molecule Toll-like receptor (TLR)-2 was significantly lower in T2DM patients compared with controls, and this difference was associated with marked variation in the composition of gut microbiota. 44 Inflammation has also been recognized as the pathogenic link between obesity and T2DM. Indeed, it is remarkable that obese individuals are not all alike in terms of susceptibility to metabolic diseases and, hence, cardiovascular risk.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…In NOD and BBDP mice treated with probiotics, there is an increase in the tight-junction protein claudin coupled with reduced systemic inflammation outlining the importance of gut-derived action on mucosal barrier wall functionality in diabetes associated inflammation [28,42,68]. One study also identified that gut-microflora-mediated epigenetic changes to the TLRs in the gut epithelium could regulate the immune response affecting the diabetic phenotype [69] …”
Section: Gut Microflora Affects Inflammatory State In Diabetes and Nementioning
confidence: 99%